Pain Relief From Analgesics to Alternative Therapies - Maldonado, Cecilia (IntechOpen, 2017)
Since the beginning of times, pain treatment has been the motive of research giving birth to multiple groups of pharmacological families and therapies. Pain perception is a construction built over the biological phenomenon of signal transduction surrounded by different factors such as gender, age, and sociocultural status, among others. The concept of pain as the solely biological manifestation of defense is nowadays considered as a narrow-minded view of this topic. In this regard concepts such as newborns feel no pain or older people complain about everything therefore should not be paid attention when referring pain, are being left behind in the understanding that pain alleviation is a human right and everybody feeling pain should be helped for its relief. This book comprises many aspects of pain treatment and the drugs involved in it. From old analgesics with new mechanisms of action for pain alleviation to analgesics potential for diminishing oxidative stress; from pharmacological therapies to electrical ones, going through alternative medicine; and from pain treatment in dentistry to chronic pain therapies, also boarding the treatment of migraine, different experts share their knowledge on the topic.